2023
DOI: 10.3390/cells12202487
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Thyroid Hormone Transporter Mct8/Oatp1c1-Deficient Mice Reveals Novel Dysregulated Target Molecules Involved in Locomotor Function

Devon Siemes,
Pieter Vancamp,
Boyka Markova
et al.

Abstract: Thyroid hormone (TH) transporter MCT8 deficiency causes severe locomotor disabilities likely due to insufficient TH transport across brain barriers and, consequently, compromised neural TH action. As an established animal model for this disease, Mct8/Oatp1c1 double knockout (DKO) mice exhibit strong central TH deprivation, locomotor impairments and similar histo-morphological features as seen in MCT8 patients. The pathways that cause these neuro-motor symptoms are poorly understood. In this paper, we performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…It is tempting to speculate that the changes are due to other molecules rather than TH, although no other substances have been identified as being trans-ported by Mct8 apart from TH. A recent study in mice with a dKO of the Mct8 and Oatp1c1 transporters identified many proteins that showed altered expression profiles compared with WT mice [32]. Not all of these proteins were associated with TH signaling, suggesting molecules other than TH are transported and exert an effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate that the changes are due to other molecules rather than TH, although no other substances have been identified as being trans-ported by Mct8 apart from TH. A recent study in mice with a dKO of the Mct8 and Oatp1c1 transporters identified many proteins that showed altered expression profiles compared with WT mice [32]. Not all of these proteins were associated with TH signaling, suggesting molecules other than TH are transported and exert an effect.…”
Section: Discussionmentioning
confidence: 99%